Thallus structural alterations in green-algal lichens as indicators of elevated CO2 in a degassing volcanic area - Bernardo, Filipe (2020)
We hypothesize that the thalli of the green-algal, CO2-sensitive lichen Usnea rubicunda (Stirton) undergo significant structural alterations as a biological response indicating increased CO2 emissions. To test that, U. rubicunda thalli were transplanted from a reference site with no volcanism into 36 sites distributed within the volcanically active Furnas caldera, encompassing the gradient of soil diffuse CO2 degassing areas (700 t d−1 of hydrothermal CO2). After 6 months of exposure in similar macroclimatic conditions, both Furnas transplants and samples kept at the reference site were retrieved for histology to assess thalli structure and the proportion between the symbionts. On average, cross-sections of Furnas thalli were significantly thicker than reference, owing mostly to the fungal layers of medulla and central cord. The latter occupied a significantly greater than reference relative volumetric density despite a smaller than reference relative percentage of algal occupation on Furnas thalli. These results reveal a positive and time-integrated response of U. rubicunda to the greater availability of CO2 from hydrothermal emissions in the volcanic environment, translated in greater efficiency of the algae in sustaining the fungal biomass. Histomorphometric structural alterations in the heteromerous thalli of U. rubicunda are suitable response biomarkers with potential to indicate a global rise of CO2 levels in natural environments.